2019
DOI: 10.1080/15412555.2019.1608172
|View full text |Cite
|
Sign up to set email alerts
|

Blood Eosinophil Counts, Withdrawal of Inhaled Corticosteroids and Risk of COPD Exacerbations and Mortality in the Clinical Practice Research Datalink (CPRD)

Abstract: Although recently introduced in the pharmacological treatment algorithm of chronic obstructive pulmonary disease (COPD), there is a need for more data supporting the use of blood eosinophil counts as a biomarker to guide inhaled corticosteroids (ICS) therapy. The aim of this study was to evaluate the risk of moderate and/or severe exacerbations and all-cause mortality in a large primary care population after withdrawal of ICS compared to continued users stratified by elevated blood eosinophil counts. In this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 35 publications
0
17
0
1
Order By: Relevance
“…Hx atopy, allergic rhinitis. Blood eos > 5% IgE > 100FEV1% predicted 55.5 ± 18Mean 31.9% patients AECOPD in 12 months prior to study enrolment.Recorded 6-monthly patient reviews59%43%Not statedSuissa 2018 [36]24,732 patients≥55 years.COPD new users of LAMA or LABA+ICS from 1.1.02.Blood eosinophil count before cohort entryInitiated on LAMA & LABA+ICS at same time.Asthma NOT excludedNot knownRecord drawn from READ code.Mean 33.6% patients had ≥1 AECOPD in 12 months prior to study enrolment0%0%Prior to study entry.Oshagbemi 2018 [37]32,693 patients≥40 year.New diagnosis COPD from 1.1.05Asthma.Any previous AECOPD.ICS use in past yearNot knownRecord drawn from READ code14%0%Single eosinophil measure at point closest to index date (start of follow-up)Oshagbemi 2019 [38]48,157 patients≥40 year.New diagnosis COPD from 1.1.05Asthma.AECOPD in 6 months prior to index dateNot knownRecord drawn from READ code18%28%Single eosinophil measure at point closest to index date (start of follow-up)Suissa 2019 [39]3954 patients≥55 years.new use LAMA or LABA+ICS from 1.1.02.Blood eosinophil count before cohort entryAsthmaFEV1% predicted53.9% (LABA + LAMA)52.7% (LABA + ICS)Record drawn from READ code.Mean 41% of patients had ≥1 AECOPD in 12 months prior to study enrolment77% (LABA+LAMA)49.1% (LABA + ICS)37% (LABA+LAMA)52.8% (LABA+ICS)Baseline…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hx atopy, allergic rhinitis. Blood eos > 5% IgE > 100FEV1% predicted 55.5 ± 18Mean 31.9% patients AECOPD in 12 months prior to study enrolment.Recorded 6-monthly patient reviews59%43%Not statedSuissa 2018 [36]24,732 patients≥55 years.COPD new users of LAMA or LABA+ICS from 1.1.02.Blood eosinophil count before cohort entryInitiated on LAMA & LABA+ICS at same time.Asthma NOT excludedNot knownRecord drawn from READ code.Mean 33.6% patients had ≥1 AECOPD in 12 months prior to study enrolment0%0%Prior to study entry.Oshagbemi 2018 [37]32,693 patients≥40 year.New diagnosis COPD from 1.1.05Asthma.Any previous AECOPD.ICS use in past yearNot knownRecord drawn from READ code14%0%Single eosinophil measure at point closest to index date (start of follow-up)Oshagbemi 2019 [38]48,157 patients≥40 year.New diagnosis COPD from 1.1.05Asthma.AECOPD in 6 months prior to index dateNot knownRecord drawn from READ code18%28%Single eosinophil measure at point closest to index date (start of follow-up)Suissa 2019 [39]3954 patients≥55 years.new use LAMA or LABA+ICS from 1.1.02.Blood eosinophil count before cohort entryAsthmaFEV1% predicted53.9% (LABA + LAMA)52.7% (LABA + ICS)Record drawn from READ code.Mean 41% of patients had ≥1 AECOPD in 12 months prior to study enrolment77% (LABA+LAMA)49.1% (LABA + ICS)37% (LABA+LAMA)52.8% (LABA+ICS)Baseline…”
Section: Resultsmentioning
confidence: 99%
“…In three of the observational studies [35, 36, 39] the proportion of patients reported to have experienced ≥1 exacerbation in the past 12 months was between 32 & 41%. The remaining two observational studies excluded patients who had experienced an exacerbation either in the 6 months prior to the index date [38] or at any point in the past [37]. COPD patients with the greatest degree of airflow impairment may experience the largest number of exacerbations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with ⩾300 blood eosinophils•µL −1 had a higher risk of exacerbation after ICS withdrawal [11,27]. However, a recent database study that evaluated the association between eosinophil counts and COPD exacerbation or all-cause mortality reported that ICS withdrawal did not increase the risk, even in patients with eosinophilia [28]. Because our study only included patients who were discharged before March 2016, it is unlikely that recent studies referring to the role of blood eosinophil counts induced confounding by indication.…”
Section: Discussionmentioning
confidence: 99%
“…A contradictory study, also based on the CPRD, was published in COPD this year, which showed that withdrawal of ICS in 48 157 participants with COPD resulted in a lower risk of moderate or severe exacerbations regardless of peripheral blood eosinophil count [12]. People with a diagnosis of asthma were excluded; however, it was not specified that the blood eosinophil measurement was taken prior to enrolment, the definition of an exacerbation was based purely on coding and the data were not linked to HES.…”
Section: Commentarymentioning
confidence: 99%